(untitled) (Journal of Fiber Bioengineering and Informatics, 2021)
In order to promote the development of universal fashion design, this paper designs and develops leg warmer, which meets the special demands for the people with lower limb dysfunction, with regards to warmth, style, aesthetics and convenience. It refers to two types of them, namely polio and spinal cord injury. First, through literature review and experimental research on thermal imaging camera temperature measurement, the paper finds people with lower limb dysfunction more sensitive to low temperature and their objective body surface temperature is lower than that of people who do not have a disability. Furthermore, the size between the legs is usually different. The survey and interview together with the research on existing products, revealed that there is a large demand for the special structure and function of the leg warmers due to the movement obstacles which are yet prevalent. The product, with the focus on close fitting, flexibility and warmth, uses light-weight fabrics and warm keeping materials which tend to be active or good at preserving the warmth. Finally, combined with the circumstances where it is used, three design schemes are proposed, including the inner closed leg warmer, the outer open close leg warmer and the outer combined waist warmer and leg warmer. After, one of them use the functional yarn which is called full-spectrum heat storage polyamide 6 fiber yarn (77.8dtex/48-68F) to make finished products and then be tested. Also, this paper proposes the design concept of multiple sizes and general adaptability of the same double leg warmer. Moreover, the sample of leg warmers is completed. The research of this paper is of fundamental importance and valuable for the future development and application of leg warmer for the people with lower limb dysfunction.